IMPLEMENTASI KEBIJAKAN REKAYASA LALU LINTAS : STUDI KASUS SISTEM SATU ARAH DAN U-TURN DI KOTA PEKANBARU - Lailatul Indriani; Dedi Kusuma Habibie (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study aims to analyze the Implementation of Traffic Engineering Policy: A Case Study of One-Way and U-Turn Systems in Pekanbaru City and identify inhibiting factors in its implementation. The background of this study is based on traffic problems such as congestion and accidents that are increasing along with the growth of motorized vehicles that are not balanced by adequate road infrastructure. The Pekanbaru City Government through the Transportation Agency has implemented various traffic engineering policies, including the one-way system and the closure of U-Turns at certain points. The method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results of the study indicate that the implemented policies have had a positive impact, but their implementation still faces obstacles such as lack of public awareness, limited infrastructure, and less than optimal coordination between institutions. This study recommends the need for more massive socialization and increased synergy between institutions to support the successful implementation of traffic engineering policies.